Teachers' Difficulties in Conducting PAI Learning Evaluation (Assessment Rubric) - Bambang Samsul Arifin; Sarah Nofis A’raaf; Mulyawan Safwandy Nugraha; Siti Rosyidah; Uswatun Hasanah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Assessment is one of the external factors that greatly affects learners' learning outcomes. Assessment aims to help learners identify and recognize the difficulties they face in learning activities. One of the principles of assessment is comprehensive and continuous, thus teachers must use a variety of appropriate assessment techniques and cover all aspects of competence to monitor the development of students' abilities. One of the assessment media uses an assessment rubric. This writing method focuses on library research, which is a research that focuses on collecting library data. A rubric is a tool that contains a set of criteria (things that become objectives) used to measure/assess performance/tasks. Rubrics are also commonly used in assessing a performance. An assessment rubric has four main components, namely task description, assessment category, category description and rating scale plus a title. These components are written in the rubric format according to the needs. There are two types of assessment rubrics, namely holistic and analytic types. The preparation can follow the stages of rubric writing, starting from determining the purpose of the assessment to the final stage of receiving input and making revisions and adjustments to the assessment rubric.